Penyuluhan Perdarahan Masa Nifas Pada Kader Di Posyandu Desa Kairatu - Windatani Mayasari; Marwia Samal (Poltekkes Kemenkes Denpasar, 2020)
World Health Organization (WHO) data shows that 99% of maternal deaths due to childbirth or birth problems occur in developing countries. When compared with the ratio of maternal mortality in nine developed countries and 51 Commonwealth countries, the ratio of maternal mortality in developing countries is the highest with 450 maternal deaths per 100 thousand live births. Post-partum bleeding is diagnosed when the amount of bleeding is considered to be more than normal. Clinical signs and symptoms of blood loss include weakness, sweating, and tachycardia which usually occur after the loss of 15-25% of total blood volume loss. Hemodynamic reduction only occurs in blood loss of 35% and 45%.Keywords: Posyandu Cadres, Puerperal Bleeding